Extrusion Characteristics of Cereal and Legume Flours. - Akinjayeju, Oluwole (Obafemi Awolowo University, 2014)
Some physical factors that determine the extrusion characteristics of cereal-legume blends were examined. These were particle size, substitution level and type of legumes. Corn (Zea mays L.), Cowpea (Vigna unguiculata) and Winged beans ( Psophocar tetragonolobus L.) of three particle sizes namely flour (<:425 microns), grits (>425 microns, <600 microns) and coarser grits (>600 microns,< 850 microns) were used. Blends containing 10% and 20% of each legume with the respective corn fraction were prepared and analysed for proximate composition, water absorption capacity, pasting (cooking) characteristics and viscosity.